Presence of Saprolegnia spp. (Oomycetes) in the Sivanamman Pond and its Characteristic Features - Digamadulla, K. M. D. S.; Sivashanthini, K.; Thavaranjit, A. C. (Faculty of Science, University of Jaffna, 2015)
Simultaneous improvisation in expertise and facilities in disease diagnosis have led to the identification of several previously unknown pathogens and diseased conditions. Saprolegniosis is one of the disease for which no known remedies were discovered yet. The current research was intended to study the presence and characterization of Saprolegnia spp. The study results hoped to be beneficial to many aspects of aquaculture and research on Saprolegniosis. Water sample was collected from Sivanamman pond (9°40'50.9N" and 80°01'43.6"E). Saprolegnia spp. was isolated by baiting method under in vitro condition. Identification and characterization was carried out on cultural, vegetative and sexual characteristics featured by Saprolegnia spp. under microscopic observation. Isolate was identified as an aquatic fungus belongs to Saprolegnia spp. with respect to the sporulation from zoosporangium and sexual reproductive structures. The sexual morphologies were significant after a starvation (26 days) in the PDA. Eucarpic mycelium was transparent, vacuolated cytoplasm contained several nuclei and produced differential oogonium with oospores. The results of present study reveal the occurrence of Saprolegnia spp. in Jaffna urban ponds and evidently prove that the mold is administrable in PDA medium.
Keywords: Fish disease; Oomycetes; Saprolegniosis